The first Ukrainian permanent GNSS station in Antarctica: processing and analysis of observation data - Savchyn, I.; Otruba, Yu.; Tretyak, K. (Ukrainian Antarctic Journal, 2021)
The main purpose of this work is to study and analyze the coordinate time series of the first Ukrainian permanent Global Navigation Satellite System (GNSS) station in Antarctica — Antarctic Station Academic Vernadsky (ASAV). We also aimed to do a comprehensive study of geophysical factors on the coordinate time series values and determine the values of the displacement components of this GNSS station. Processing of measurements was performed using the software Bernese GNSS Software v.5.2. The Bernese Processing Engine (BPE) module and the RNX2SNX (RINEX-TO-SINEX) processing algorithm were used to obtain daily solutions of permanent GNSS station ASAV. Daily solutions of the permanent GNSS station ASAV and the vector of its displacements were determined in the coordinate system IGb08. The vector of the permanent GNSS station ASAV has a northeasterly direction. The obtained results are consistent with the model of tectonic plate movements of this region. To study the characteristic periods of harmonic oscillations of coordinate time series of permanent GNSS station ASAV due to various geophysical factors. A set of studies was conducted, which included the development of an algorithm and a package of applications for processing time series and determining optimal curves that most accurately describe them. Thus, for each time series, the original equation is used to determine the optimal period of oscillation. As a result, an anomalous distribution of fluctuations in the values of permanent GNSS station ASAV with different periods was revealed — this indicates the complex nature of the influence of geophysical factors on the spatial location and confirms the need for systematic studies of such factors on the stability and displacement of GNSS station. It is established that the permanent GNSS station ASAV is exposed to seasonal oscillations, associated with changes in environmental conditions.